The mneme - Semon, Richard Wolfgang (Minnesota Filiquarian Publishing LLC, 1921)
Originally published in 1921. The Mneme by Richard Wolfgang Semon is presented here in a high quality paperback edition. This publication was produced from a professional scan of an original edition of the book, which can include imperfections from the original book or through the scanning process, and has been created from an edition which we consider to be of the best possible quality available. This popular classic work by Richard Wolfgang Semon is in the English language. The Mneme is highly recommended for those who enjoy the works of Richard Wolfgang Semon, and for those discovering the works of Richard Wolfgang Semon for the first time.